Essays in Development Economics - MORANDO, BRUNO (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Economics, 2020)
This dissertation is a collection of three essays with a geographical and thematic common denominator. The broad objective of the thesis is to study how the Ugandan agricultural sector is affected by the country'
APPROVED
Keywords: Agriculture; Uganda; Misallocation